Survey on MOOCs for Digital Game based Learning for Learners - Chavan, Shivendra; Bedekar, Mangesh (International Journal of Computer Sciences and Engineering, 2025)
The Massive Open Online Courses (MOOCs) require extrinsic or intrinsic to the low level of completion of the training, and encounter problems with the interactivity and engagement of students throughout the MOOCs that can transform the enthusiasm of the students in boredom, and then to abandon it at any time. To attract the best players to MOOCs, gamification has been implemented on many platforms; especially since gamification became a buzzword in 2012. This research project examines the motivation and training as perceived by participants in MOOCs, using innovative educational strategies for teaching community in the field of education. In learning gamification, the use of Digital Game Learning (GBL) it provides more fun learning than gamification. In this regard, the current implementation of gamification, DGBL and their role in MOOCs will be assessed.